BASIC PRINCIPLES OF PEDAGOGICAL DESIGN IN THE EDUCATIONAL PROCESS - Allayorov Muzaffar Mingaliyevich (Western European Studies, 2024)
This article explores the integration of structured educational content and student activities as a cohesive technological process within the educational framework. Focused on imparting fundamental aspects of social experience, the study justifies the main principles of pedagogical design. The article delves into the application of diverse methods and tools to enhance the effectiveness of the educational process.
Keywords: Subject; reflexive; result; technologist